Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 14. Beitrag. Coleoptera: Cleridae. - Gnadt, Wolfgang (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The material of the Goleopterus family Cleridae collected by the Albania-expedition of the Deutsches Entomologisches Institut contains 27 specimens representing 5 species 3 of which are new to the fauna of Albania. There are now 7 species of the Cleridae known from Albania.